The effect of self-regulated learning in higher education with online project-based collaborative learning models - Permadi, Pradana Din; Masitoh, Siti; Arianto, Fajar (Edelweiss Applied Science and Technology, 2025)
This study investigates the effect of implementing an online project-based collaborative learning model on students’ self-regulated learning in higher education, particularly in media development courses. Using a quantitative approach with a one-group pretest–posttest design, data were collected from 34 undergraduate students selected randomly from three different majors. A self-regulated learning questionnaire was administered before and after the intervention over one semester. The findings revealed a significant improvement in students’ self-regulated learning following the application of the model (Sig. = 0.000 < 0.05), with mean scores increasing from 58.94 (pretest) to 73.74 (posttest). These results indicate that online project-based collaborative learning fosters critical components of self-regulation, such as goal setting, monitoring, strategy use, and reflection. The study highlights the potential of integrating project-based and collaborative online approaches to enhance independent learning, communication, and problem-solving skills in digital learning environments. Further research is recommended to explore the model’s effectiveness across various educational levels and disciplines and its integration with other instructional strategies to optimize learning outcomes.